2020
DOI: 10.1101/2020.04.27.20077180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19-induced acute respiratory failure – an exacerbation of organ-specific autoimmunity?

Abstract: Background: Understanding the pathophysiology of respiratory failure (ARDS) in coronavirus disease 2019 (COVID-19) patients is of utmost importance for the development of therapeutic strategies and identification of risk factors. Since we observed clinical and histopathological similarities between COVID-19 and lung manifestations of connective tissue disease (CTD-ILD) in our clinical practice, aim of the present study is to analyze a possible role of autoimmunity in SARS-CoV-2-associated respiratory failure. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
0
26
0
4
Order By: Relevance
“…Additionally, hyperactivation of pre-existing T cells can contribute to short-and long-term disease severity via inflammation and autoimmunity, as increased production of IFN-γ by CD4 + and CD8 + T cells has been observed in severe COVID-19 patients (Wang et al, 2020). Furthermore, it has been reported (Ehrenfeld et al, 2020) that SARS-CoV-2 infection can be a triggering factor for autoimmune reactions and severe pneumonia with sepsis leading to acute respiratory distress syndrome (ARDS), bone-marrow affection with pancytopenia and organ-specific autoimmunity (Gagiannis et al, 2020;Henderson et al, 2020;Hersby et al, 2020). Importantly, pre-existing T cell immunity can influence vaccination outcomes, as they can induce a faster and better immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hyperactivation of pre-existing T cells can contribute to short-and long-term disease severity via inflammation and autoimmunity, as increased production of IFN-γ by CD4 + and CD8 + T cells has been observed in severe COVID-19 patients (Wang et al, 2020). Furthermore, it has been reported (Ehrenfeld et al, 2020) that SARS-CoV-2 infection can be a triggering factor for autoimmune reactions and severe pneumonia with sepsis leading to acute respiratory distress syndrome (ARDS), bone-marrow affection with pancytopenia and organ-specific autoimmunity (Gagiannis et al, 2020;Henderson et al, 2020;Hersby et al, 2020). Importantly, pre-existing T cell immunity can influence vaccination outcomes, as they can induce a faster and better immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an online pre-published study from Germany the authors studied prospectively a group of 22 patients for the possible role of autoimmunity in SARS-CoV-2 -associated respiratory failure. Based on serological, radiological and histomorphological similarities between Covid-19-associated ARDS and acute exacerbation of connective tissue disease induced interstitial lung disease, the authors suggest that SARS-CoV-2 infection might trigger or simulate a form of organ specific autoimmunity in predisposed patients [27]. In a similar retrospective study from China of 21 patients with critical SARS-CoV-2 pneumonia, the authors showed a prevalence of between 20 and 50% of autoimmune disease related autoantibodies, suggesting the rational for immunosupression in such cases of Covid-19 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Conditions in which the immune system attacks its own tissues are usually associated with development of autoAbs. Indeed, Gagiannis et al, studied prospectively a group of 22 patients for the possible role of autoimmunity in COVID-19 patients [ 155 ]. AutoAb titers ≥1:100 were detected in 10/11 COVID-19 patients who required intensive care treatment, and in 4/11 patients with milder clinical course.…”
Section: Covid-19—autoimmune or Autoinflammatory Disorder?mentioning
confidence: 99%